2017
DOI: 10.12705/663.9
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐Paratethyan origin and Middle to Late Miocene principal diversification of the Lactucinae (Compositae: Cichorieae) inferred from molecular phylogenetics, divergence‐dating and biogeographic analysis

Abstract: The Lactucinae or Lactuca alliance include approximately 200 species distributed across the Northern Hemisphere and Africa. They were not recognised as a separate lineage until the late 20th century and their circumscription is still not fully settled. The generic classification of no other group of the Cichorieae has faced as many controversies as the Lactuca alliance and competing taxonomies coexist. This paper provides the first molecular phylogeny of the subtribe on a global scale as a major step towards i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
121
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(132 citation statements)
references
References 72 publications
(87 reference statements)
8
121
2
1
Order By: Relevance
“…A sister group relationship between subtribes Hyoseridinae (four Sonchus species) and Crepidinae ( Nabalus albus and Taraxacum kok‐saghyz ) was revealed in all analyses of our Cichorieae tribe‐wide data sets (Table ; 24 samples). This is promising because the separation of subtribes Crepidinae and Lactucinae has proven complicated (see Kilian et al., ), yet Crepidinae is always sister to Hyoseridinae rather than to Lactucinae in our analyses (Fig. ; Appendices , ).…”
Section: Discussionmentioning
confidence: 92%
“…A sister group relationship between subtribes Hyoseridinae (four Sonchus species) and Crepidinae ( Nabalus albus and Taraxacum kok‐saghyz ) was revealed in all analyses of our Cichorieae tribe‐wide data sets (Table ; 24 samples). This is promising because the separation of subtribes Crepidinae and Lactucinae has proven complicated (see Kilian et al., ), yet Crepidinae is always sister to Hyoseridinae rather than to Lactucinae in our analyses (Fig. ; Appendices , ).…”
Section: Discussionmentioning
confidence: 92%
“…This seems surprising in view of their previous classification as members of Lactuca or the Lactucinae. It must be considered, however, that the generic concept of Lactuca in the late 19th and early 20th century was extremely wide and spanned members of several of the modern subtribes (Kilian et al, 2017). Disentangling the subtribes Lactucinae and Crepidinae has, moreover, proven particularly difficult due to the scarcity of nonhomoplastic morphological synapomorphies (Bremer, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The Dubyaea-Nabalus-Soroseris-Syncalathium clade has been resolved in several studies with varying partial representation of its members (Kilian et al, 2009a;Zhang et al, 2011;Liu et al, 2013;Kilian et al, 2017). Estimations divergence times for the Crepidinae by Zhang et al (2011) revealed that the Dubyaea-Nabalus-Soroseris-Syncalathium clade is likely of Pliocene origin, with a crown age of around 5 myr only; for genera such as Soroseris or Syncalathium a crown age of less than 2 and 3 myr, respectively, have been estimated.…”
Section: Discussionmentioning
confidence: 99%
“…L. sativa is distantly related to, and less crossable with, the species L. saligna. The most recent common ancestor (MRCA) for L. saligna and L. serriola has been dated, by a phylogenetic study with nuclear (ITS) and chloroplast sequences, to between 3.4 and 2 MYA (Kilian et al 2017). Phenotypically, the divergence between L. saligna and L. sativa is clearly demonstrated by the observation of nearly complete sterility in the F1 hybrid and hybrid breakdown in the F2 population.…”
Section: Discussionmentioning
confidence: 99%